(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Lyahotska L. L. New approaches and tools of implementation of open education and distance learning. The author reveals the role of open educational and distance learning in order to ensure greater access to quality education and lifelong learning. The paper deals with basic approaches to implementation of the principles and technologies of open education in the educational process in Ukraine.